A Self-Stabilized Inverted Pendulum Made of Optically Responsive Liquid Crystal Elastomers - Cheng, Quanbao; Zhou, Lin; Li, Kai (Frontiers in Robotics and AI, 2022)
The inverted pendulum system has great potential for various engineering applications and its stabilization is challenging because of its unstable characteristic. The well-known Kapitza's pendulum adopts the parametrically-excited oscillation to stabilize itself, which generally requires complex controller. In this paper, self-sustained oscillation is utilized to stabilize an inverted pendulum, which is made of a V-shaped optically-responsive liquid crystal elastomer (LCE) bar under steady illumination. Based on the well-established dynamic LCE model, a theoretical model of the LCE inverted pendulum is formulated, and numerical calculations show that it always develops into the unstable static state or the self-stabilized oscillation state. The mechanism of the self-stabilized oscillation is originated from the reversal of the gravity moment of the inverted pendulum accompanied with its own movement. The critical condition for triggering self-stabilized oscillation is fully investigated, and the effects of the system parameters on the stability of the inverted pendulum are explored. The self-stabilized inverted pendulum does not need additional controller, and offers new designs of self-stabilized inverted pendulum systems for potential applications in robotics, military industry, aerospace and other fields.